THE ANALYSIS AND ESTIMATION OF AN INEQUALITY OF DISTRIBUTION OF INCOMES IN UKRAINE - Меркулова, Т. В.; Забуга, С. И.; Зернов, А. И. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2013)
In given the work the concept of distribution of incomes, its quantity indicators, a problem of an inequality of incomes is considered. Computation of various indicators of an inequality of distribution, Gini coefficient, an average return, the median income, the modal income is conducted, dynamics of these indicators from 2000 to 2010 is considered. Also, by means of the constructed models, the interrelation of various indicators of an inequality of distribution of incomes of the population, and also their influence on monthly average value of gross national product per capita and an index of physical volume of gross national product is considered.